# What is the equation of the normal line of #f(x)=(1-x)e^(3x)-e^x# at #x=1#?

graph{((1-x)e^(3x)-e^x-y)(y+e-1/(e(e^2+1))(x-1))=0 [-3.844, 4.926, -3.28, 1.103]}

The general equation for normal is

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the normal line of f(x)=(1-x)e^(3x)-e^x at x=1 is y = -2x + 2.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the slope of the line normal to the tangent line of #f(x) = xe^(x-1)+x^3 # at # x= 2 #?
- If the tangent line of #f(x)# at (6,3) passes through the point (0,2), what is #f'(6)#?
- How do you find the equation of tangent line to the curve #f(x)= x^3+x^2+x+1# at x=4?
- What is the equation of the normal line of #f(x)=x/lnx# at #x=4 #?
- Differentiate #f(x)=2x-3# using first principal?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7